Self-assembly of organometallic Pd(II) complexes via CH3 center dot center dot center dot pi interactions: the first example of a cyclopalladated compound with herringbone stacking pattern - De Almeida, E. T.; Mauro, A. E.; Santana, A. M. [UNESP]; Ananias, S. R. [UNESP]; Netto, A. V. G. [UNESP]; Ferreira, J. G.; Santos, R. H. A. (Elsevier B.V., 2007)
Two binuclear cyclometallated compounds [Pd(C-2,N-dmba)(mu-N-3)](2) (1) and [Pd-2(C-2,N-dmba)(2)(mu-N-3)(mu-Cl)] (2) (dmba = N,N-dimethylbenzylarnine) have been synthesized and characterized by elemental 3 analysis, IR and NMR spectroscopies and single crystal X-ray diffraction crystallography. The ability of CH3 groups to form C(sp(3))-H...pi hydrogen bonds with phenyl rings is responsible for the molecular self-assembly within the crystals of 1 and 2. Compound 1 crystallizes as one-dimensional supramolecular chains whereas the crystal packing of 2 consists of a herringbone of sandwiches composed by two inversely related [Pd-2(C-2,N-dmba)(2)(mu-N-3)(mu-Cl)] molecules. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: supramolecular chemistry; C(sp(3))-H...pi interactions; cyclopalladated compounds; self-assembly